Visible light-driven photocatalytic Heck reaction over carbon nanocoil supported Pd nanoparticles. Issue 21 (30th September 2016) - Guo, Xiao-Wei; Hao, Cai-Hong; Wang, Cheng-Yu; Sarina, Sarina; Guo, Xiao-Ning; Guo, Xiang-Yun
Abstract : This paper presents a carbon nanocoil supported Pd nanoparticle system (Pd/CNCs) as a photocatalyst for coupling reaction of aryl halides and alkenes (Heck reaction) at 40 °C. Abstract : Pd nanoparticles supported on carbon nanocoils (Pd/CNCs) show unexpectedly high photocatalytic activity for coupling reaction of aryl halides and alkenes (Heck reaction) at 40 °C. The energetic electrons in Pd nanoparticles, excited via interband transitions under visible light irradiation, can transfer to halogen atoms to facilitate the cleavage of carbon–halogen bonds in aryl halides, which requires rather high temperature in the thermal process. Then, the final products can be fast achieved by alkene insertion and β-hydrogen elimination processes.